Boosted solar water photoreduction by conjugated polymer-mediated tandem charge transfer. (19th January 2023) - Liu, Jinyuan; Zhu, Shumin; Wang, Bin; Wang, Rong; Yang, Ruizhe; Zhu, Xingwang; Song, Yanhua; Xu, Hui; Li, Huaming
Abstract: Semiconductor materials anchored with transition metal cluster are promising photocatalysts for photocatalytic hydrogen evolution. In this paper, Co, N-co-doped graphene modified thin mesoporous carbon nitride (Co-NG/TMCN) was be synthesized through electrostatic adsorption treatment. Extensive characterization was used to explore the morphology, structures and optical properties of the as-prepared photocatalysts. The 10 wt% Co-NG/TMCN exhibited the high photocatalytic hydrogen evolution rate (2949 μmol g −1 ) within 4 h visible light irradiation, which was about 113 times than that of the pure TMCN (26 μmol g −1 ). Co-NG material with excellent electrical conductivity played a major role in accelerating charge transfer from TMCN material to cobalt atomic clusters. The photocatalytic hydrogen evolution performance of Co-NG/TMCN material was effectively improved. Consequently, a feasible approach for doping transition metal clusters to enhance photocatalytic activity was provided. Highlights: The introduction of cobalt atomic clusters provided more active sites. The synergy between Co, N-co-doped graphene and thin mesoporous carbon nitride was beneficial to the ficient separation of photogenerated electrons. The low content cobalt atomic clusters were efficiently utilized to increase hydrogen production rate.